2014
DOI: 10.7860/jcdr/2014/9327.4426
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy with Gilbert Syndrome – A Case Report

Abstract: A primigravida presented to us at 32 weeks of gestation with vomiting, myalgia and jaundice. On examination she had icterus, she was dehydrated, uterus was corresponding to dates and the fetal heart rate was good. On evaluation, all the investigations were normal except mild unconjugated hyperbilirubinaemia and hypoglycaemia. Based on the above findings we derived at a diagnosis of Gilbert syndrome. Dehydration due to vomiting aggravated her jaundice. On correcting her dehydration jaundice resolved, patient im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Of note, there is only one case report by Mohan et al which reported a favourable obstetric outcome which was similar with this case. 7 Despite the positive outcome in this case, Madam SABM experienced anxiousness throughout her six years follow up due to her undiagnosed problem which heightened during current pregnancy. Her experience concurred with the finding from Bronner et al whereby high anxiety score was found during patients' diagnostic phase.…”
Section: Discussionmentioning
confidence: 64%
“…Of note, there is only one case report by Mohan et al which reported a favourable obstetric outcome which was similar with this case. 7 Despite the positive outcome in this case, Madam SABM experienced anxiousness throughout her six years follow up due to her undiagnosed problem which heightened during current pregnancy. Her experience concurred with the finding from Bronner et al whereby high anxiety score was found during patients' diagnostic phase.…”
Section: Discussionmentioning
confidence: 64%
“…Dehydration, fasting or stress can cause episodes of Gilbert's syndrome. Bilirubin is an endogenous antioxidant, and hyperbilirubinaemia associated with this condition is typically mild and less than 6 mg/dl [8].…”
Section: Discussionmentioning
confidence: 99%
“…In Gilbert's syndrome, patients experience recurrent mild jaundice. To diagnose Gilbert's syndrome, other genetic causes of hyperbilirubinaemia, such as Criggler-Najjar syndrome, must be ruled out [8]. The diagnosis of Gilbert's syndrome can be made using various methods, such as the alkaline methanol method, thin layer chromatography and High-Performance Liquid Chromatography (HPLC), which allow for the precise separation and measurement of bilirubin in its conjugated and unconjugated forms [10].…”
Section: Discussionmentioning
confidence: 99%
“…GS is a benign condition of mild unconjugated hyperbilirubinemia with no deteriorating effect on liver. Approximately 7% of a general population has this disease, with men being more commonly affected than women (ratio 2-7:1) [10].…”
Section: Discussionmentioning
confidence: 99%